Production of antibacterial peptide variants microcin J25 and its activity test in the Mycobacterium tuberculosis RNA polymerase - Zevallos Aliaga, Dahlin (2019)
The success of rifampin as anti-tuberculosis therapy indicates that the inhibition of RNA polymerase (RNAP) of Mycobacterium tuberculosis (MtbRNAP) is an effective strategy, however, resistance to this antibiotic is increasing. This is why, the finding of new inhibitors for MtbRNAP would be a great contribution to the fight against tuberculosis. Microcin J25 (MccJ25) is an antibiotic peptide whose main molecular target is the RNA polymerase of Escherichia coli (EcoRNAP). Biochemical studies have determined that MccJ25 binds and obstructs the secondary channel of EcoRNAP, in addition, have identified the regions of MccJ25 that are responsible for this interaction. They also demonstrated that MccJ25 inhibits RNA polymerases from bacteria phylogenetically related to E.coli, but has no inhibitory activity on the RNAPs of bacteria related to the Mycobacterium genus. The computational analysis indicates that the structure of the secondary channel of EcoRNAP and MtbRNAP is conserved, but it has some differences in the amino acid sequence, giving mccJ25 its differential activity. In this work, I propose to produce variants of MccJ25 through randomly modifying the amino acid sequence and test its inhibitory activity into MtbRNAP. The variants will be produced by PCR- mediated overlap method, the resultants products will be inserted in a plasmid that permit expression the variants in the interior of a reporter bacteria, E.coli strain that permit measure the activated of the MtbRNAP inside of the cell. In this way, will be performed high- throughput screening of the MccJ25 mutant effects on MtbRNAP. Although the variants of MccJ25 produced by this work will not be used directly as an anti-tuberculosis drug, these results could initiate the development of a new therapy.